The Role of Cognitive Ability in Mediating Active Learning and Learning Discipline on Learning Achievement - Novemasari, Dionasius; Sunarto, Sunarto (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study aims to test the role of cognitive ability in mediating active learning and learning discipline on learning achievement. This research is a quantitative study with practical significance and data collection. The analysis technique used was regression analysis, and Sobel test. The results obtained that active learning has significant positive effect on cognitive abilities. Learning discipline has no effect on cognitive abilities. Active learning has no effect on learning achievement. Learning discipline has significant positive effect on learning achievement. Cognitive ability has no effect on learning achievement. Cognitive ability does not function to mediate active learning and learning discipline on learning achievement. The findings suggest prioritizing learning discipline to enhance learning achievement while focusing on active learning to boost cognitive abilities, providing actionable insights for educators and policymakers. The novelty lies in this integrated and region specific exploration that challenges existing educational theories and provides tailored insights for practical implementation. The research contributes to understanding the nuanced relationships between active learning, discipline, cognitive ability, learning achievement among sixth grade students. It provides actionable insights for educators, policymakers, and future researchers to develop more holistic strategies for enhancing learning achievement.